2008
DOI: 10.1097/pas.0b013e31812f6ba6
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 Expression in Brain Tumors: A Reflection of the Neuroglial Differentiation Pathway

Abstract: Sox2 is a key transcription factor that maintains the proliferation of neuroglial stem cells and inhibits neuronal fate commitment. Moreover, it was recently found that brain tumors contain stem cells that resemble normal neuroglial stem cells in many respects. This study was undertaken to describe Sox2 expression in various brain tumors, and to determine whether Sox2 expression is a universal feature of brain tumors, or whether its expression is limited to a specific lineage of brain tumors. Sox2 immunohistoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
73
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 23 publications
9
73
0
Order By: Relevance
“…Many markers potentially specific for GSCs have been proposed such as A2B5 cell surface ganglioside epitope (A2B5) [26,27], aldehyde dehydrogenase (ALDH) [28], BMI1 polycomb ring finger oncogene (BMI1) [29,30], fucosyltransferase 4 (FUT4) (CD15) [31], Thy-1 cell surface antigen (Thy-1) (CD90) [32], prominin-1 (PROM1) (CD133) [5,6], chemokine (C-X-C motif) receptor 4 (CXCR4) [33], inhibitor of DNA binding 1 (ID1) [34], integrin α6 (ITGA6) [35], L1 cell adhesion molecule (L1CAM) [36], maternal embryonic leucine zipper kinase (MELK) [37], musashi-1 (msi1) [38], nestin (NES) [38][39][40], octamer-binding transcription factor 4 (OCT4) [41], OLIG2 [42] and SOX2 [38,[43][44][45]. Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Many markers potentially specific for GSCs have been proposed such as A2B5 cell surface ganglioside epitope (A2B5) [26,27], aldehyde dehydrogenase (ALDH) [28], BMI1 polycomb ring finger oncogene (BMI1) [29,30], fucosyltransferase 4 (FUT4) (CD15) [31], Thy-1 cell surface antigen (Thy-1) (CD90) [32], prominin-1 (PROM1) (CD133) [5,6], chemokine (C-X-C motif) receptor 4 (CXCR4) [33], inhibitor of DNA binding 1 (ID1) [34], integrin α6 (ITGA6) [35], L1 cell adhesion molecule (L1CAM) [36], maternal embryonic leucine zipper kinase (MELK) [37], musashi-1 (msi1) [38], nestin (NES) [38][39][40], octamer-binding transcription factor 4 (OCT4) [41], OLIG2 [42] and SOX2 [38,[43][44][45]. Among these, much attention has been given to CD133, which is currently used to identify and isolate GSCs [40,43,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…27 Chen et al 28 These observations indicate that SOX2 has a role in tumorigenicity of both gliomas and lung adenocarcinomas in vivo; however, its exact molecular mechanisms are still elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinds of tumors, including lung, stomach, breast cancers and gliomas, showed SOX2 overexpression. [41][42][43][44] Recently, two studies demonstrated that SOX2 expression was correlated with lymph node metastasis, distant spread, and poor prognosis in colorectal carcinoma patients. 31,45 The NOTCH signaling pathway is an evolutionarily conserved intercellular signal transfer system regulating cell differentiation, proliferation, and apoptosis.…”
Section: Modern Pathology (2013) 26 1123-1131mentioning
confidence: 99%